Temperature‐based targeting in a multispecies fishery under climate change. (30th December 2015) - Dunn, Daniel C.; Moxley, Jerry H.; Halpin, Patrick N.
Abstract: Temperature controls important physiological processes in fish and determines aspects of their niches. In an effort to inform selective fishing and spatiotemporal management in the U.S. Northeast Multispecies fishery, we used 16 years of data from the Northeast Fisheries Science Center Spring and Fall Scientific Trawl Surveys to determine if bottom temperature can be used to differentiate the distribution of Atlantic cod ( Gadus morhua ) from other species within the fishery management plan (FMP). We identified two separate regimes in spring temperatures and used empirical cumulative distribution functions to calculate biomass availability by temperature for each species. We applied a bagged approach to find optimum thermal threshold values that maximize the difference in cod biomass from each of the other species. For our study area, 38% to 54% of the species considered were well separated from cod by temperature in spring, whereas only 17% were separable in the fall. This study suggests that temperature targeting can be used seasonally to separate cod from many other species in the FMP including top catches and no‐retention species. The use of temperature targeting may allow fishermen to better meet multiple quotas while avoiding choke species. Our results also suggested increasing thermal overlap between cod and species inhabiting higher median temperatures (e.g., spiny dogfish, Squalus acanthias ) under the current warming temperature regime. These results indicate that the ability to selectively fish in the US Northeast Multispecies fishery will become more difficult under a warming ocean.